Absolute and relative differential blood count predicts survival of AJCC stage I‐II melanoma patients scheduled for sentinel lymph node biopsy. (12th February 2020) - Wagner, Nikolaus B; Luttermann, Felix; Gassenmaier, Maximilian; Forschner, Andrea; Leiter, Ulrike; Garbe, Claus; Eigentler, Thomas K
Abstract: Background/Objectives: Elevated neutrophil‐to‐lymphocyte ratio (NLR) in peripheral blood is associated with poor overall survival (OS) in metastatic melanoma patients receiving immunotherapy. However, the impact of peripheral blood cells in patients undergoing sentinel lymph node biopsy (SLNB) is still unclear. This study was intended to characterize the impact of peripheral blood leukocytic cells on overall survival (OS) in melanoma patients undergoing SLNB. Methods: A total of 1412 AJCC stage I‐II melanoma patients scheduled for SLNB at a single institution in the period 2010–2015 with available perioperative blood tests were randomly assigned to two independent cohorts. Associations of peripheral blood leukocytes with OS were analysed using Kaplan–Meier estimator and multivariate Cox proportional hazards model. Results: NLR >4.26, absolute neutrophil count >5800/µL, relative neutrophil count >69.7% and relative lymphocyte count ≤ 17.5% were significantly associated with reduced OS in both cohorts. Absolute monocytes >810/µL, absolute eosinophils ≤200/µL, relative monocytes >6.6%, relative eosinophils ≤2.7% and relative basophils ≤0.6% were significantly associated with reduced OS in one cohort each. On multivariate analysis, a combined score including absolute levels of neutrophils, lymphocytes, monocytes and eosinophils was significantly associated with OS in both cohorts. The hazard ratio of patients with a risk score of 3–4 was 5.42 (95% confidence interval: 1.52–19.42, P  = 0.0094) in cohort 1 and 9.42 (2.06–43.06, P  = 0.0038) in cohort 2, respectively. Conclusions: We conclude that peripheral blood leukocytes are independently associated with OS in stage I‐II melanoma patients and should be considered as prognostic markers in these patients. Eosinophils and basophils deserve more attention in future investigations.